Hitting the Jackpot – development of gas chromatography–mass spectrometry (GC–MS) and other rapid screening methods for the analysis of 18 fentanyl‐derived synthetic opioids. Issue 6 (13th February 2020) - Gilbert, Nicolas; Antonides, Lysbeth H.; Schofield, Christopher J.; Costello, Andrew; Kilkelly, Brenda; Cain, Alan R.; Dalziel, Paula R.V.; Horner, Karen; Mewis, Ryan E.; Sutcliffe, Oliver B.
Abstract: In recent years, the occurrence of synthetic opioid fentanyl and its derivatives has grown significantly in forensic casework. This study presents the synthesis and analysis of 18 fentalogs, selected based on information received from local law enforcement. This study provides colorimetric tests, thin‐layer chromatography (TLC) which can potentially be utilized for presumptive screening of the target compounds, as bulk powders or as trace‐level adulterants. The fully validated confirmatory GC–MS method (employing SIM mode) allows the identification of the 18 derivatives, five commonly encountered controlled substances and four adulterants, within 20 minutes. The cross‐validated method described herein provides a sensitive screening and quantitation method for the illicit (and potentially harmful) components at trace levels (LOD = 0.007–0.822 μg/mL and LOQ = 0.023–2.742 μg/mL respectively). Spectral data [ 1 H‐NMR, 13 C‐NMR, 19 F‐NMR, FT‐IR, and HRMS] and assignments for the synthesized reference materials are also provided in the Supplementary Information for laboratories engaged in the routine analysis of fentanyl and its derivatives. Abstract : This study details the analysis of 18 synthesized fentalogs encountered in forensic drug casework using presumptive testing, thin layer chromatography (TLC), and gas chromatography–mass spectrometry (GC–MS). The validated GC–MS method provides a general screening method and quantification of the active components within seized solid samples. NMR, FT‐IR, and HRMS data are provided in the ESI for laboratories engaged in the routine analysis of these materials.